Chemical Composition of the Essential Oil of Pituranthos scoparius - Yousfi, Mohamed; Gourine, Nadhir; Merrad, Bahia; Stocker, Pierre; Gaydou, Emile M (Natural product communications, 2011)
The essential oils obtained by hydro distillation of the aerial parts of Pituranthos scoparius were collected from different regions of Algeria and gave various yields ranging from 0.6 up to 2.8% (v/w). These samples were analyzed by GC and GC-MS showing the occurrence of monoterpene hydrocarbons and some oxygenated compounds. The major components were α-pinene (4.4-35.8%), limonene (0.8-66.5%), bornyl acetate (tr-9.6%), myristicin (tr-31.1) and dill apiole (0.4-47.3%). The aerial parts of P. scoparius could be either very rich or very poor in limonene, myristicin or dill apiole. Cluster analysis shows differences in essential oil compositions of samples coming from the different area collected.
Keywords: Pituranthos scoparius; essential oil; monoterpene; myristicin; dill apiole; cluster analysis